Human TCR repertoire in cancer - Lin Chen; Yuan Hu; Bohao Zheng; Limei Luo; Zhenzhen Su (Cancer Medicine)
Abstract Background T cells, the “superstar” of the immune system, play a crucial role in antitumor immunity. T‐cell receptors (TCR) are crucial molecules that enable T cells to identify antigens and start immunological responses. The body has evolved a unique method for rearrangement, resulting in a vast diversity of TCR repertoires. A healthy TCR repertoire is essential for the particular identification of antigens by T cells. Methods In this article, we systematically summarized the TCR creation mechanisms and analysis methodologies, particularly focusing on the application of next‐generation sequencing (NGS) technology. We explore the TCR repertoire in health and cancer, and discuss the implications of TCR repertoire analysis in understanding carcinogenesis, cancer progression, and treatment. Results The TCR repertoire analysis has enormous potential for monitoring the emergence and progression of malignancies, as well as assessing therapy response and prognosis. The application of NGS has dramatically accelerated our comprehension of TCR diversity and its role in cancer immunity. Conclusions To substantiate the significance of TCR repertoires as biomarkers, more thorough and exhaustive research should be conducted. The TCR repertoire analysis, enabled by advanced sequencing technologies, is poised to become a crucial tool in the future of cancer diagnosis, monitoring, and therapy evaluation.